Design of a Virtual Platform to Counter Economic Recession - Schardosin F.Z. (2022)
© 2022, IFIP International Federation for Information Processing.This paper aims to present the proposal of a platform founded on a Virtual Breeding Environment (VBE) as an alternative for resource sharing, survival, and growth of organizations that were impacted by the economic recession caused by COVID-19. Considering this, an informational platform model is presented, based on the theoretical framework of VBE and the potential to meet the needs of actors who are part of this environment. The result is a platform called Collabore. This platform helps with resource sharing between companies and enables the development of new network technologies. It also facilitates the co-creation of value between actors, allows lobby creation to compete with large companies in the global market, ensures new jobs and income generation, and facilitates the collaboration between companies dispersed globally, connected by Information and Communication Technologies (ICTs).